Pengaruh Social Media Marketing dan Perceived Value Terhadap Purchase Intention - Martin Leonardo Silitonga (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
Technology is bringing social media to people and businesses alike, turning social media into a marketing medium for everyone, from small groups to huge industries such as smartphones. Social media can be used as a marketing platform to develop a community by businesses to customers, who can make the best decision from thousands of options available from experience and references that motivate them to suit their needs for a new smartphone. Social media marketing is a powerful tool for businesses to promote their products. It can influence purchase intention by giving an informative posting on social media that can also attract customers, even without perceived value, so businesses should use it. This study aims to determine the impact of social media marketing and perceived value on purchase intention. The methods used for this study are quantitative studies with a sample of 109 undergraduate students who do not buy smartphones and have already watched any marketing that smartphone use on social media. This study found that social media marketing positively impacts purchase intention, while perceived value harms purchase intention. Companies should push more content to social media to the customer as it will give the brand more attention to the public, and consumers will preview the item for themselves and make a purchase decision.